Pelatihan Peningkatan Kemampuan Memori Otak dan Digitalisasi Pembelajaran Sains dengan Pemanfaatan Media Pembelajaran Interaktif: ThingLink - Utami, Ika Wahyu; Suudi, Bambang Cholis; Putri, Larasati Rizky; Farhan, Ahmad; Najih, Muhammad; Mustafidan, Ahmad Roqy; Ismail, Muhammad Luthfi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2025)
The digital era has brought major changes to the education, including Science learning at the junior high school level. However, science learning at the junior high school level still needs several challenges, such as a lack of variety in learning media, low interest in learning science, and limited students' ability to understand science concepts. Based on these problems, the Physics Laboratory of Universitas Trisakti held a Community Service (PkM) activity in collaboration with MGMP IPA of Tangerang. Service activities are carried out in the form of training for science teachers with training materials to improve brain memory abilities and training on the digitalization of science learning with ThingLink interactive media. Teachers are often faced with various challenges in teaching, including the complexity of science material, the rapid development of science and the high workload of teachers. Training to improve brain memory abilities can help improve teachers' ability to remember information, focus and concentrate. Furthermore, training on digitizing science learning using ThingLink is considered important to carry out. ThingLink is a digital platform that allows the creation of interactive science learning content, simulations and virtual experiments that are interesting and easy for students to understand. This PkM activity can increase teacher competency and professionalism in teaching, so that it can improve the quality of science learning in the classroom. This training can be carried out sustainably by collaborating with more educational partners.